PENGARUH PENAMBAHAN HIDROKOLOID TERHADAP KARAKTERISTIK FISIK DAN SENSORIS NORI FUNGSIONAL DAUN SINGKONG - Sholitan, Nur Wahyu; Fitriani, Afrianita; Innayatuhubbah, Gesti Annisa; Nurlaily, Desi Anisa; Widowati, Esti (Jurnal Teknologi Hasil Pertanian, 2017)
The present research sought to find out appropriate type and concentrations of hydrocolloids in the production of nori derived from cassava leaves, and the influence on physical, chemical, and sensory properties of the produced nori. The research is useful to optimize the use of cassava leaves as alternative raw materials for the production of nori. Hydrocolloids with concentrations of 1%, 3%, and 5% were added in boiled and blended cassava leaves, with the addition of 1 gram of salt and 100 ml of water. Such processes as molding, drying, and frying were subsequently done. The given concentrations of hydrocolloids were proved to influence smell, texture, overall, and thickness, instead of color. The functional food of nori derived from cassava leaves appropriate with commercial nori seaweed is that with the addition of pectin concentration of 3%.